2019
DOI: 10.1038/s41467-019-09289-5
|View full text |Cite
|
Sign up to set email alerts
|

FBXW2 suppresses migration and invasion of lung cancer cells via promoting β-catenin ubiquitylation and degradation

Abstract: FBXW2 inhibits proliferation of lung cancer cells by targeting SKP2 for degradation. Whether and how FBXW2 regulates tumor invasion and metastasis is previously unknown. Here, we report that FBXW2 is an E3 ligase for β-catenin. FBXW2 binds to β-catenin upon EGF-AKT1-mediated phosphorylation on Ser 552 , and promotes its ubiquitylation and degradation. FBXW2 overexpression reduces β-catenin levels and protein half-life, whereas FBXW2 knockdown increases β-catenin levels, protein half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 56 publications
2
62
0
Order By: Relevance
“…2A). We have recently defined the consensus-binding motif (TSXXXS) required for FBXW2 to bind to its substrates, such as SKP2 (22) and β-catenin (23). Examination of the MSX2 protein sequence indeed identified such a motif, which is evolutionarily conserved ( 43 SSLPFS 48 ) (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A). We have recently defined the consensus-binding motif (TSXXXS) required for FBXW2 to bind to its substrates, such as SKP2 (22) and β-catenin (23). Examination of the MSX2 protein sequence indeed identified such a motif, which is evolutionarily conserved ( 43 SSLPFS 48 ) (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FBXW2 (F-box and WD repeat domain containing 2) plays a role in the regulation of protein polyubiquitination, cellular protein modification process, proteolysis. Yang found that FBXW2 can participate in the occurrence and development of lung cancer by regulating epidermal growth factor-AKT1, β -catenin [ 44 ]. There are few reports related to FBXW2 involving in pain regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, β-catenin can directly activate the transcription of E-box repressors Snail, Slug, and Twist to promote epithelial-mesenchymal transition and facilitate metastasis (Yang et al, 2013). In addition, β-catenin enhances the mobility of metastasizing cancer cells by activating the transcription of a panel of different metalloproteinases (MMPs) to contribute to the remodeling of the extracellular matrix (Lowy et al, 2006;Kamino et al, 2011;Yang F. et al, 2019). Regulation of MMPs by several mechanisms including transcriptional activation via promoter and via miRNAs plays important roles in the remodeling of extracellular matrix (Surgucheva et al, 2003;Surgucheva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%